Automated individualization of dialysate sodium concentration reduces intradialytic plasma sodium changes in hemodialysis - Ságová, Michaela; Wojke, Ralf; Maierhofer, Andreas; Gross, Malte; Canaud, Bernard; Gauly, Adelheid (Artificial organs, 2019)
In standard care, hemodialysis patients are often treated with a center-specific fixed dialysate sodium concentration, potentially resulting in diffusive sodium changes for patients with plasma sodium concentrations below or above this level. While diffusive sodium load may be associated with thirst and higher interdialytic weight gain, excessive diffusive sodium removal may cause intradialytic symptoms. In contrast, the new hemodialysis machine option "Na control" provides automated individualization of dialysate sodium during treatment with the aim to reduce such intradialytic sodium changes without the need to determine the plasma sodium concentration. This proof-of-principle study on sodium control was designed as a monocentric randomized controlled crossover trial: 32 patients with residual diuresis of ≤1000 mL/day were enrolled to be treated by high-volume post-dilution hemodiafiltration (HDF) for 2 weeks each with "Na control" (individually and automatically adjusted dialysate sodium concentration) versus "standard fixed Na" (fixed dialysate sodium 138 mmol/L), in randomized order. Pre- and post-dialytic plasma sodium concentrations were determined at bedside by direct potentiometry. The study hypothesis consisted of 2 components: the mean plasma sodium change between the start and end of the treatment being within ±1.0 mmol/L for sodium-controlled treatments, and a lower variability of the plasma sodium changes for "Na control" than for "standard fixed Na" treatments. Three hundred seventy-two treatments of 31 adult chronic hemodialysis patients (intention-to-treat population) were analyzed. The estimate for the mean plasma sodium change was -0.53 mmol/L (95% confidence interval: [-1.04; -0.02] mmol/L) for "Na control" treatments and -0.95 mmol/L (95% CI: [-1.76; -0.15] mmol/L) for "standard fixed Na" treatments. The standard deviation of the plasma sodium changes was 1.39 mmol/L for "Na control" versus 2.19 mmol/L for "standard fixed Na" treatments (P = 0.0004). Whereas the 95% CI for the estimate for the mean plasma sodium change during "Na control" treatments marginally overlapped the lower border of the predefined margin ±1.0 mmol/L, the variability of intradialytic plasma sodium changes was lower during "Na control" versus "standard fixed Na" treatments. Thus, automated dialysate sodium individualization by "Na control" approaches isonatremic dialysis in the clinical setting.
Keywords: individualizovaná medicína; Sodium; Female; klinické křížové studie; Renal Dialysis; chronické selhání ledvin; dialýza ledvin; automated sodium adjustment; ženské pohlaví; dialyzační roztoky; lidé; Cross-Over Studies; Algorithms; Kidney Failure, Chronic; prospektivní studie; Dialysis Solutions; Male; sodík; Aged; Prospective Studies; dialysis fluid; sodium; algoritmy; lidé středního věku; Precision Medicine; senioři; mužské pohlaví; hemodialysis; Middle Aged; Humans